Lombok Treaty and Strengthening Regional Identity: Its Impact on Australia, Indonesia, and Global Stability - Harry Darmawan; Ni Luh Pingkan Amalia Pratama Putri; Irma Indrayani (JURNAL PARADIGMA : Journal of Sociology Research and Education, 2023)
This article examines the role of the Lombok Agreement in strengthening regional identity and its implications for Australia, Indonesia and global stability. Signed in 2006, this treaty forms the basis of bilateral cooperation between important countries in the Asia-Pacific. This research analyzes how the agreement has enhanced regional identity and mutual understanding and overcome historical, cultural and political differences. The study examines the historical context of the treaty, its key provisions, implementation challenges and achievements since 2006 and its impact on bilateral relations, including trade, security cooperation and cultural exchanges. This study also examines the impact of the treaty on regional dynamics in ASEAN and the wider Asia-Pacific region. This study also assesses the treaty's contribution to the formation of a shared regional identity and its impact on global stability, particularly in managing regional tensions and promoting the peaceful resolution of conflicts. Using a qualitative approach, this research will analyze diplomatic communications, policy documents and official statements. In-depth interviews will also be conducted with diplomats, policymakers and regional experts to gain insight into the treaty's implementation and impact. This approach allows for a comprehensive and contextual understanding of the complex dynamics surrounding the Lombok Treaty and its impact on regional identity. The results show that the Lombok Treaty has significantly enhanced regional cooperation, increased a sense of shared identity, and promoted stability in the Asia-Pacific region. This study concludes that this kind of treaty has the potential to be applied as a model and has broad implications for international relations theory, particularly in the context of understanding formal agreements that aim to shape regional identity and at the same time maintain global stability.